2017
DOI: 10.1080/10717544.2017.1381198
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: a calixarene derivative micelle potentiates anti-breast cancer stem cells effects in xenografted, triple-negative breast cancer mouse models

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous and clinically aggressive disease with no approved targeted therapy. Curcumin has shown therapeutic potential against TNBC, but it shows low bioavailability and low efficacy when administered as a free drug. Here we describe a novel vehicle for in vivo delivery of curcumin based on the phosphorylated calixarene POCA4C6. Curcumin-loaded POCA4C6 micelles (CPM) were prepared using the thin-film method and they showed a unilamellar structure with an average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…Moreover, Calix [4]arene, bearing methylenebisphosphonic groups, can host cationic small drugs such as carboplatin or metal ions such as Cu 2+ or Fe 2+ in its cavity [10,16,17]. In previous work, we showed that micelles similar to PM in the present study delivered anti-cancer drugs in response to pH [54,55]. In that study, the micelles had shorter n-hexyl chains, which we lengthened to n-dodecyl chains for this study to create larger micelles for higher drug loading.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, Calix [4]arene, bearing methylenebisphosphonic groups, can host cationic small drugs such as carboplatin or metal ions such as Cu 2+ or Fe 2+ in its cavity [10,16,17]. In previous work, we showed that micelles similar to PM in the present study delivered anti-cancer drugs in response to pH [54,55]. In that study, the micelles had shorter n-hexyl chains, which we lengthened to n-dodecyl chains for this study to create larger micelles for higher drug loading.…”
Section: Discussionsupporting
confidence: 54%
“…The uptake of the cell monolayer shown above might not exactly imitate the behavior of the nanoparticles within the solid tumor due to more complex situations such as modest drug permeation, distorted enzyme activities, and escalated oxygen tension present in the solid tumor. [35] To mimic that actual situation, 3D tumor spheroids were constructed to investigate the uptake of the nanoparticles. The distributions of Rh-B@ZnS in U87 tumor spheroids were weak, indicating Rh-B@ZnS had difficulties in diffusing into hidden territories of the tumor spheroid.…”
Section: Cellular Internalization Studymentioning
confidence: 99%
“…Curcumin analogs with improved bioavailability and tumor retention showed improved efficacy in the treatment of TNBCs [ 292 , 293 ]. The reduced bioavailability of curcumin was overcome by facilitating in vivo delivery of curcumin through novel curcumin-loaded phosphorylated calixarene POCA4C6 micelles [ 294 ]. In TNBC cells, the micelles efficiently caused G2/M cell cycle arrest and inhibited proliferation, invasion, migration, and tumor spheroid formation, with associated induction of apoptosis and reduction in the levels of AR and nuclear β-catenin [ 294 ].…”
Section: Phytochemicals As Anticancer Compounds Effective In the Tmentioning
confidence: 99%
“…The reduced bioavailability of curcumin was overcome by facilitating in vivo delivery of curcumin through novel curcumin-loaded phosphorylated calixarene POCA4C6 micelles [ 294 ]. In TNBC cells, the micelles efficiently caused G2/M cell cycle arrest and inhibited proliferation, invasion, migration, and tumor spheroid formation, with associated induction of apoptosis and reduction in the levels of AR and nuclear β-catenin [ 294 ]. The curcumin-loaded micelles had improved retention in TNBC tumor xenografts of BalB/c nude mice and inhibited tumor growth without any systemic toxicity [ 294 ].…”
Section: Phytochemicals As Anticancer Compounds Effective In the Tmentioning
confidence: 99%